Suspicion on the Non-conformity of the Goods as a Foundation of Breach of International Sales Contract - Latifah, Emmy; Bajrektarevi, Anis H.; Salsabila, Dini Kartika (Faculty of Law, Hasanuddin University, 2024)
The aim of the research is to analyze the breach of international sales contract based on suspicion on non-conformity of the goods in regards to United Nations Convention on Contracts for the International Sale of Goods (CISG). This study is normative legal research. The types of approach used are the legislative approach, case approach, and conceptual approach. The analysis technique uses syllogistic methods through deductive thinking patterns. The result of the study indicates that the appropriate reason of suspicion of non-conformity of the goods under Article 35 of the CISG is the effect of suspicion on the usability of the goods rather than the existence of suspicion itself. It is required the most influence factor in having adverse effect on the function of the goods to be categorized as non-conformity of the goods in regards to a breach of contract. Suspicion could be removed by ensuring that the goods are functional. Finally, the burden of proof towards the suspicion on the non-conformity of the goods could be liable by the parties, especially the seller.